Creative counseling: Integration of counseling in cognitive behavior therapy groups with passive music therapy to improve self-efficacy of students of millennial - Situmorang, Dominikus David Biondi; Mulawarman, Mulawarman; Wibowo, Mungin Eddy (Universitas Negeri Padang, 2018)
The aim of this study is to determine the effectiveness of group counseling with cognitive behavior therapy approach using passive music therapy technique to improve the self-efficacy of millennials college students who is writing thesis. The research used quasi-experimental design (pretest, post-test,and follow-up). Group counseling was conducted for five meetings, and follow-up was performed two weeks after the treatment. Research subjects were seven millennials college students. Purposive sampling technique was used to select the subjects, that is based on inclusion criteria and level of self-efficacy which is obtained from self-efficacy scale (rxy=0.601-0.839,coefficient alpha=0.951).The results showed that group counseling with cognitive behavior therapy approach using passive music therapy technique was significantly effective to improve the millennials college students’ self-efficacy in pretest vs. post-test and pretest vs follow-up, but in post-test vs. follow-up there was a slight decrease in self-efficacy. Passive music therapy which is integrated into group counseling with cognitive behavior counseling approach, it is not only able to solve the individual problems but also able to help individuals to analyze their thoughts and behaviors through passive music activities with guidedimagery.